Beverages in child nutrition - A.I. Safronova; E.A. Pyr'eva; O.V. Georgieva (LCC «Medicine-Inform», 2022)
A.I. Safronova, E.A. Pyr'eva, O.V. Georgieva Federal Research Center for Nutrition & Biotechnology, Moscow, Russian Federation Abstract Dietary patterns established at a young age have a significant impact on eating disorders. Therefore, the impact of individual food products is crucial. This paper discusses the use of drinks in early childhood nutrition, given novel ideas on the effects of specific nutrients on a child's health. The most disputable issue is the intake of simple carbs found in drinks. Currently, no guidelines on controlling added sugars in children under two years are available. The paper addresses the drink types containing carbohydrates included in childhood nutrition and the nutritional value of juices of various substrates. Foreign and Russian recommendations on quantitative limitations of high-carbohydrate beverages in childhood nutrition (given the effect of their overconsumption on the development of metabolic disorders) are highlighted. The authors describe specialized juice-containing beverages for childhood nutrition, requirements for manufacturing, and enri chment with nutrients. The assessment results on the nutrient content of juices for child nutrition are discussed. Finally, current trends in the manufacturing of juice-containing drinks and their role in providing young children with nutrients are uncovered. Keywords: children, juices, drinks, nutrients, simple carbs. For citation: Safronova A.I., Pyr'eva E.A, Georgieva O.V. Beverages in child nutrition. Russian Journal of Woman and Child Health. 2022;5(1):78-84 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-78-84.